Social worker intervention with client families from National Health Institute “ Honorio Delgado- Hideyo Noguchi" - Chuchón Calle, Vilma (2001)
The treatment of mental illness cannot be approached in isolation, without considering the family members, as well as their group and community environment. This systemic-relational view is closely related to the levels of intervention of the Social Worker, in which the individual is not observed in isolation, but in relation to the other, in mutual affectation. The social network included in the individual-family, group and community organization and development Social Work, constitute personal, environmental, family and service organization communication channels, necessary especially in the intervention with the family and the patient with mental disorder.